2024
DOI: 10.1039/d4ee00710g
|View full text |Cite
|
Sign up to set email alerts
|

The acupuncture effect of carbon nanotubes induced by the volume expansion of silicon-based anodes

Ziying He,
Chenxi Zhang,
Yukang Zhu
et al.

Abstract: The cyclic instability of Si-based anodes can be effectively alleviated by adding carbon nanotube (CNT) networks. However, the ion diffusion and electrochemical performance vary greatly depending on the type of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…(Figure 1g, Table S2). 26 Combined with the above electrochemical analysis, it can be concluded that the addition of SWCNT can not only promote the reaction kinetics of the SiO-based electrode but also stabilize the interface and achieve long cycling life.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…(Figure 1g, Table S2). 26 Combined with the above electrochemical analysis, it can be concluded that the addition of SWCNT can not only promote the reaction kinetics of the SiO-based electrode but also stabilize the interface and achieve long cycling life.…”
Section: Resultsmentioning
confidence: 80%
“…Thanks to the outstanding mechanical and conductive properties, carbon nanotubes (including single-walled and multiwalled carbon nanotubes, SWCNT and MWCNT) are demonstrated as one type of near-perfect additive for further enhancing the application of Si-based anode materials. For example, Wei et al revealed that SWCNT could maintain the complete conductive/structural networks even under tensile stresses up to 6.2 GPa for SiO@C . Recently, they further found that the longer and slender SW/MW-CNTs additives exhibited a limited acupuncture effect caused by SiO x volume-change-induced compressive stress during the cycling process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation